Haplotype-based association of renin gene polymorphisms with essential hypertension in Han population of northern china. (December 2017) - Zhang, Guoping; Li, Xueyan; Zhang, Keyong; Zhao, Jingbo; Qiu, Changchun
Introduction: The renin gene has been suggested as a good candidate in the study of genetic mechanism of essential hypertension. However, studies on the contribution of renin gene polymorphisms to essential hypertension, have not had consistent outcomes. The purpose of the present study is to explore the association of renin gene polymorphisms with essential hypertension in the Han population of northern China. Methods: A case-control study was conducted among 3090 Han farmers (1533 essential hypertension patients and 1557 normotensives). Genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism and polymerase chain reaction-sequencing. Results: The genotypic and allelic distributions of rs2368564 in essential hypertension and control was significant statistically ( p <0.001). The allelic distribution of rs10900557 showed marginal statistical significance ( p =0.048). There were no significant differences in other genotypic and allelic distributions ( p >0.05). In the haplotypes comprised by the six single-nucleotide polymorphisms, there were differences in the distribution of haplotypes A-T-C-G-C-A, A-T-C-G-C-G, G-C-T-G-T-A and G-C-T-G-T-G in both groups, and their differences reached to significant levels, respectively. After having corrected for false discovery rate, this association still remained significant. Conclusions: The current study provides evidence for a possible association of renin gene polymorphisms with essential hypertension in a Han population of northern China.